A gamification framework for research productivity enhancement on the higher education institution - Ahmad Sanmorino; Luis Marnisah; Hastha Sunardi (Institute of Advanced Engineering and Science, 2021)
The condition of research productivity in higher education institutions in Indonesia is still not ideal. Departing from this problem, this paper aims to contribute in the form of a framework used as the main alternative in optimizing research productivity, including the number of publications in higher education institutions. The mechanism proposed is a framework that uses designs derived from games or better known as gamification. Based on the preliminary testing of the proposed framework, it shows that each construct of the framework has a positive impact on research productivity enhancement as the final goal. One of the constructs is Network has a positive impact of 0.415 on Behavior, the Behavior has a positive impact of 0.403 on research productivity enhancement. This also applies to other constructs. Except for the Points that donot have good reliability, it will become homework in future studies.